Minimum acceptable diet and contributing factors among children aged 6–23 months in Afghanistan: insights from the 2022–2023 Multiple Indicator Cluster Survey - Essa Tawfiq; Muhammad Haroon Stanikzai; Massoma Jafari; Ghulam Mohayuddin Mudaser; Zainab Ezadi; Sayed Ali Shah Alawi; Abdul Wahed Wasiq; Omid Dadras (BMC Nutrition)
Abstract Background Undernutrition among children is a public health concern in most low and middle-income countries (LMICs) and is associated with poor child growth and development. Knowledge about child feeding practices is needed for nutritional policies and programs. Hence, this study assessed the status of minimum acceptable diet (MAD) and its associated factors among children aged 6–23 months in Afghanistan. Methods This cross-sectional study was based on a secondary dataset of the 2022–2023 Afghanistan Multiple Indicator Cluster Survey (MICS 2022–23). Complete data from 7,876 children aged 6–23 months were analysed. The outcome variable was MAD and was defined according to the WHO and UNICEF recommendations and indicators for young child feeding practices. Bivariate and multivariate binary logistic regression analyses were used to identify factors associated with MAD. Results About 7.3% of children aged 6–23 months were fed with the recommended MAD. The likelihood of receiving MAD was higher in children aged 13–18 months [adjusted odds ratio (AOR) 2.01 (95%CI: 1.63–2.48)] and 19–23 months [2.11 (95%CI: 1.68–2.66)], in children belonging to households with higher wealth status [1.39 (95%CI: 1.04–1.87), 2.06 (95%CI: 1.51–2.82), and 3.07 (95%CI: 2.14–4.40) for the 3rd, 4th, and 5th quintile of wealth status, respectively], and in children living in rural areas [1.56 (95%CI: 1.21–2.01)]. On the other hand, the maternal age group 30–39 years [0.79 (95%CI: 0.64–0.96)] and non-institutional delivery [0.67 (95%CI: 0.54–0.83)] were associated with reduced odds of MAD. Conclusion Our study revealed that a small percentage (7.3%) of children received MAD in Afghanistan. This emphasizes the need for policies and interventions aimed at the improvement of child feeding practices to ultimately lead to better child nutrition and health in Afghanistan.